La gestión del patrimonio cultural en la comunidad de Wiracochapampa para el desarrollo turístico sostenible, Distrito de Huamanchumo, Provincia de Sánchez Carrión - Departamento La Libertad - 2016 - Pérez Muñoz, César Leandro (2019)
ABSTRACT The present investigation addressed the theme: The management of cultural heritage in the community of Wiracochapampa for sustainable tourism development. District of Huamachuco, Province of Sánchez Carrión - Department La Libertad - 2016. The object of study, in the Community of Wiracochapampa, in the department of La Libertad, in the province of Sánchez Carrión and in the district of Huamachuco. It should be noted that in the place under investigation, there are many types of cultural heritage, both material and immaterial, which makes the place, a potential tourist destination that to date has been charging tourism demand, for the contribution of sustainable tourism development. The most representative cultural heritage, the Archaeological Site of Wiracochapampa, has the same name as that of the community; the place belongs to the Huamachuco Culture, with Wari influence; it is a residential-administrative-ceremonial site. The objectives set for this research were the forms of involvement of the community in the management of cultural heritage. Meanwhile, the Historical-Comparative Method and the Analytical Method, linked to the nature of the investigation. The research techniques were directly observed, interviews and surveys. The results obtained have gained the importance of cultural heritage management for the sustainable sustainable development of the community of Wiracochapampa.